Investigating the Role of BACE1 and SORL1 as Exosomal Biomarkers in Dementia among Type II Diabetic Individuals (Journal of Fatima Jinnah Medical University, 2024)
Background: Type II diabetes is the major cause of several microvascular and macrovascular complications found to alter the neurological balance within the brain and involve in cognitive impairment. BACE1 and SORL1 genes are the focus of the study, which may be involved in the cross linkage of Type II diabetes disease and dementia. This study aimed to investigate the expression of these two genes in Type II diabetic patients suffering from dementia and its correlation.Patients and methods: Blood samples from a total of 47 subjects divided into four groups (diabetes, diabetes with dementia, brain tumors patients) and 12 healthy controls were collected from Lahore General Hospital (LGH). An internationally preferred minimal mental state examination (MMSE) scoring was used (English and Urdu validated translation). The data was analysed by GraphPad Prism 9.0 and one way ANOVA was performed to find variance amongst the samples with respected to expression analysis.Results: This study included 12 healthy controls and 47 patients (22 males and 25 females) with the mean age±SD (55.9±6.2) during 8 months. BACE1 expression was significantly elevated in the dementia with diabetes group compared to healthy controls (mean difference: 2.1, 95% CI = 1.0 to 3.2, p
Keywords: Premaxillary setback; posterior vomerine ostectomy; premaxillary protrusion